Writing on water : the sounds of Jewish prayer - Frigyesi, Judit (Central European University Press, 2018)
""Writing on Water" is a first-hand account of the thoughts, lives and rituals of the secretly practicing strictly religious Jews during the era of Communism in Eastern Europe (primarily in Budapest) with especial focus on their traditional ritual chant as part of a total acoustic experience ("soundscape"). The book is based on extensive fieldwork and analysis of orally transmitted material. The subject matter is unique both in the choice of the communities and its focus on sound. I attempt to explain how melodies and soundscapes become the sustaining/protective "environment", as well as the vehicle, for the expression of world-orientation - in a situation when open speech is inconceivable. The first part of the book is a journey toward the lives/sounds of these communities, the second contains documentary interviews, and the third describes the communities' disintegration after 1990. The book conveys scholarly results through poetry, prose-poems and art-photos"--